Latihan Sirkuit 5 Pos untuk Meningkatkan Kebugaran Jasmani Siswa di Masa Pandemi - Andy Supriady (STKIP Paasundan Press, 2021)
This study aims to see the effect of 5 Post Circuit exercises and Cross Country exercises to improve students' physical fitness, which was carried out by Junior High School students during the pandemic. The method used is experimental. The population in this study were 20 students of class 8A SMPN Padalarang. The instruments used are the Indonesian Physical Fitness Test for junior high school (SMP) level: 50-meter sprint test, 30-second body lift test, 60-second lying down test, upright jump test and 1000-meter long-distance running test. The results of the analysis of 5 items of physical fitness test with an average category of being. It can be concluded that the 5 post circuit training and cross-country training have a significant effect on increasing students' physical fitness during the pandemic.